A Review of the Rulings by Muslim Jurists on Assisted Reproductive Technology and Reproductive Tissue Transplantation - Matthews, Zachariah (Religions, 2021)
Developments in organ donation and transplantation continue to generate controversy, especially in the field of reproductive medicine. Techniques used in assisted reproductive technology (ART), such as artificial insemination, in vitro fertilisation (IVF), gestational surrogate mothering and gender selection, continue to challenge conventional norms. The use of these techniques, as well as the transplantation of reproductive tissue such as ovaries and the testicles, for example, enables children to be conceived who may have no genetic or social relationship to one or more of their parents, biological or other. This generates religious, legal, moral and ethical dilemmas for many people, including Muslims, who tend to hold negative views about organ donation. Legal frameworks such as ijtihad (independent judgment) in conjunction with al-maqaasid al-shar’iyyah (the higher objectives of Divine decree) are assessed to review the available Sunni juristic rulings pertinent to the question, “what are the views of Muslim jurists about assisted reproductive technology and tissue transplantation given evolving implications for offspring and donors?” The review finds that a majority of Muslim jurists and juristic councils permit assisted reproductive technology and reproductive tissue transplantation with several conditions.